Resistant Genes and Multidrug-Resistant Bacteria in Wastewater: A Study of Their Transfer to the Water Reservoir in the Czech Republic - Stachurová, Tereza; Sýkorová, Nikola; Semerád, Jaroslav; Malachová, Kateřina (Life (Basel, Switzerland), 2022)
Wastewater is considered the most serious source of the spread of antibiotic resistance in the environment. This work, therefore, focuses on the fate and spread of antibiotic resistance genes (ARGs) in wastewater and the monitoring of multidrug-resistant strains. ARGs were monitored in the nitrification and sedimentation tanks of the wastewater treatment plant (WWTP) and in the dam into which this WWTP flows, at various times. The highest relative abundance was found for the blaTEM > tetW > blaNDM-1 > vanA resistance genes, respectively. An increased concentration of tetracycline (up to 96.00 ng/L) and ampicillin (up to 19.00 ng/L) was found in water samples compared to other antibiotics detected. The increased incidence of seven ARGs and four antibiotics was observed in the November and December sampling times. Isolated ampicillin-resistant strains showed a high degree of resistance to ampicillin (61.2% of the total isolates had a minimum inhibitory concentration (MIC) ≥ 20 mg/mL). In 87.8% of isolates, out of the total number, the occurrence of two or more ARGs was confirmed. These multidrug-resistant strains were most often identified as Aeromonas sp. This strain could represent a significant role in the spread of multidrug resistance through wastewater in the environment.
Keywords: antibiotic resistance gene; wastewater; tetracycline resistance; wastewater treatment plant; beta-lactam resistance; water environment; multidrug resistance